Resistance, Identity, and Colonial Perspectives: Reinterpreting Saminism as a Movement for Justice and Freedom in Colonial Java - Siska Nurazizah Lestari; Indra Fibiona; Bambang Rakhmanto (Medan Resource Center, 2026)
This article re-examines Saminism, a social movement founded by Samin Surosentiko (1859–1914) in Blora, Central Java, within the broader context of Dutch colonial domination and indigenous resistance in colonial Indonesia. The study addresses the question of how Saminism has been represented in colonial discourse and to what extent its practices can be understood as forms of anti-colonial resistance. Using a historical research method with an interpretive qualitative approach, the study analyzes colonial archives, Dutch administrative reports, colonial newspapers, ethnographic accounts, and relevant scholarly literature through the stages of heuristics, source criticism, interpretation, and historiography. The findings demonstrate that colonial authorities systematically portrayed the Samin community as backward, irrational, and resistant to progress in order to justify colonial intervention and control. However, a critical reading of the sources reveals that tax refusal, rejection of colonial regulations, egalitarian communication practices, communal economic relations, and moral reciprocity constituted deliberate and coherent strategies of resistance rooted in Javanese ethical values. The study concludes that Saminism was not merely a passive peasant movement but an alternative socio-political vision that embodied cultural sovereignty, social justice, and community autonomy, thereby highlighting the significance of everyday resistance and subaltern agency in colonial historiography.